The effect of handball invasion game model on elementary students’ empathy: A sociocultural perspective - Danang Pujo Broto; Agus Kristiyanto; Joko Nurkamto; Yudanto Yudanto (Jurnal Cakrawala Pendidikan, 2026)
This study aims to examine the effectiveness of a teacher's handbook designed for handball learning grounded in a sociocultural approach, with the objective of enhancing empathy among elementary school students. The research was motivated by global concerns regarding the decline in children's empathy, attributed to increased digitalization and limited direct social interactions, particularly in urban areas such as Sleman. Employing a quasi-experimental method with a non-equivalent control group design, the study involved two groups of students from different elementary schools. The experimental group utilized the teacher's handbook, while the control group received conventional learning. The study instruments included a validated and reliable empathy questionnaire, alongside observations of empathetic behaviors during the learning process. Statistical analysis revealed that the experimental group experienced a significant increase in empathy levels compared to the control group, with a mean difference of 6.2 points. The t-test indicated a significant value (p < 0.05), signifying a statistically significant difference between the two groups. These findings demonstrate that the sociocultural-based handball learning model is effective in fostering empathy among students and offers a practical solution for integrating character into physical education through developmentally appropriate game based learning in elementary schools.